The benefits of being understood: the role of ethnic identity confirmation in knowledge acquisition by expatriates - Fan, Shea X.; Cregan, Christina; Harzing, Anne-Wil; Köhler, Tine (2017)
In this article, we propose that the concept of ethnic identity confirmation (EIC), the level of agreement between how expatriates view the importance of their own ethnic identity and how local employees view the importance of expatriates' ethnic identity, can explain why expatriates who are ethnically similar to host-country employees are sometimes less effective than expected when working overseas. Multinationals often choose ethnically similar expatriates for international assignments, assuming these expatriates can more effectively acquire knowledge from local employees. Thus, understanding the specific challenges that endanger the realization of this potential is crucial.